Stimulating estrus and ovulation in lactating sows and consequences for pig growth - Frobose, Hyatt Lowell (Kansas State University, 2016)
A total of 188 sows and their litters were used in 2 experiments to evaluate methods to induce estrus and ovulation in lactating sows and effects on pig growth. In Exp. 1, an altered suckling method (ALT) was designed to combine split-weaning and intermittent suckling as a means to reduce the suckling stimulus in primi- and multiparous sows during the last week of lactation (d 18 to 25). The ALT sows were also removed for daily boar exposure. The ALT treatment produced lactational estrus in 75% and 95% of primiparous and multiparous sows, respectively. The ALT sows were in estrus earlier (P < 0.01) than controls post-farrowing, with no effect on subsequent reproductive performance. From d 18 to 32, the ALT treatment benefited (P < 0.01) growth of lightweight pigs but decreased (P < 0.01) BW gain of heavyweight pigs, resulting in overall similar growth. However, variation in BW was reduced (P < 0.01) by 50% for ALT litters. In Exp. 2, varying suckling reduction strategies were applied to boar-exposed lactating sows. Overall, 76% of sows in suckling reduction treatments expressed estrus in lactation. Split-weaned and ALT sows performed reproductively similar to controls, whereas sows with daily litter separation or a single 24 h litter removal tended (P < 0.10) to have reduced conception rates versus controls or split-weaned sows. Reduced suckling treatments differed in their ability to induce lactational estrus and impact on pig BW gain immediately post-weaning. However, no evidence was found of benefit for pig growth to market weight or litter BW variation. Four additional experiments using 902 nursery pigs were conducted to test the efficacy of potential detoxifying agents against deoxynivalenol (DON) in swine diets. The effects of DON were not offset by adding an algae-modified montmorillonite clay nor by a proprietary blend of preservatives and clays. However, hydrothermally treating DON-contaminated diets with sodium metabisulfite modified the structure of DON to a non-toxic DON-sulfonate adduct and restored nursery pig growth via improved (P < 0.05) ADG, ADFI and G:F.
Keywords: Deoxynivalenol; Lactational estrus; Lactating sow; Mycotoxin; Pigs; Suckling